INFECTIOUS DISEASES AS A GLOBAL PROBLEM OF MODERN TIME (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The article studies modern problems of diagnostics and the prevention of infectious diseases; A conclusion is made about infectious diseases as one of the global problems of our time